Clinical Presentation and Management of Congenital Mesoblastic Nephroma: A Case Report - E. A. Alinnor; O. C. Ugwa; I. O. Nnamani (Medical Science: Recent Advances and Applications Vol. 2, 2025)
Background: Congenital mesoblastic nephroma (CMN), a benign mesenchymal renal tumor, accounts for 2% - 3% of renal tumors in children and is the most prevalent renal tumor in neonates and infants under six months of age. It was first described in 1967. Congenital Mesoblastic Nephroma (CMN) is a mesenchymal renal tumour of early life. With a median diagnosis of two months and over 90% of cases occurring within the first year of life, it is the most prevalent non-Wilms’ renal tumour. Even though imaging can be used as a diagnosing tool, it is frequently identified in the neonatal period when the baby has an abdominal mass. There are three different histologic types: mixed, cellular, and classic. Radical nephrectomy is the usual mode of treatment, though adjuvant chemotherapy may be necessary for the cellular type, which may be aggressive. Case Presentation: A case of a 2-day-old term male neonate born to a 27-year-old mother through spontaneous vertex delivery (SVD) was reported. He presented with a right-sided abdominal mass from birth. An abdominal ultrasound scan revealed a huge, well-circumscribed heterogeneous soft tissue mass in the right hemi-abdomen extending to the left side, measuring 10.2 cm by 8.0 cm. He underwent a right radical nephrectomy with a tumour weight of 450 g and a size of 18 cm × 15 cm × 6 cm. Histopathological diagnosis was Congenital Mesoblastic Nephroma (cellular type) Stage 1. Congenital mesoblastic nephroma, Wilms’ tumor and considerably less common lesions such as a malignant rhabdoid tumor, clear cell sarcoma of the kidney (CCSK), and ossifying renal tumor of infancy are among the differential diagnoses for solid renal tumors. Conclusion: Any infant with a renal tumour should be evaluated for congenital mesoblastic nephroma. Since it can be identified early in pregnancy, it is advisable to promote fetal anomaly screening using ultrasound to prevent late presentation. CMN is usually benign, patients must undergo routine monitoring for any possible paraneoplastic syndromes. Proper follow-up is necessary in the first few years of life because certain forms of mesoblastic nephromas can potentially develop into malignancies. Detailed investigation and complete resection are fundamental for ensuring an excellent outcome.